1999
DOI: 10.1038/19986
|View full text |Cite
|
Sign up to set email alerts
|

A family of mammalian Na+-dependent L-ascorbic acid transporters

Abstract: Vitamin C (L-ascorbic acid) is essential for many enzymatic reactions, in which it serves to maintain prosthetic metal ions in their reduced forms (for example, Fe2+, Cu+), and for scavenging free radicals in order to protect tissues from oxidative damage. The facilitative sugar transporters of the GLUT type can transport the oxidized form of the vitamin, dehydroascorbic acid, but these transporters are unlikely to allow significant physiological amounts of vitamin C to be taken up in the presence of normal gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
796
3
21

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 824 publications
(854 citation statements)
references
References 26 publications
34
796
3
21
Order By: Relevance
“…Additional cAMP-dependent phosphorylation sites are present in the C-terminal of SVCT1 and SVCT2. 5,38 Activation of PKC has been shown to inhibit Then, cells were precultured in serum-free aMEM containing 1 mg/ml of indomethacin for 3 h, and then treated along with 1 mM PGE2 for additional 1 h. Immunostaining was performed by using mouse anti-myc first antibody and anti-mouse Alex555-conjugated second antibody. Stained cells were examined under an Olympus confocal microscope (bars, 100 mm) Na þ -dependent vitamin C transport in a cell line derived from rabbit nonpigmented ciliary epithelium and in oocytes expressing hSVCT1 and hSVCT2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional cAMP-dependent phosphorylation sites are present in the C-terminal of SVCT1 and SVCT2. 5,38 Activation of PKC has been shown to inhibit Then, cells were precultured in serum-free aMEM containing 1 mg/ml of indomethacin for 3 h, and then treated along with 1 mM PGE2 for additional 1 h. Immunostaining was performed by using mouse anti-myc first antibody and anti-mouse Alex555-conjugated second antibody. Stained cells were examined under an Olympus confocal microscope (bars, 100 mm) Na þ -dependent vitamin C transport in a cell line derived from rabbit nonpigmented ciliary epithelium and in oocytes expressing hSVCT1 and hSVCT2.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 AA stimulates procollagen hydroxylation, processing, and fibril assembly followed by the dramatic induction of specific genes associated with the osteoblastic phenotype, including alkaline phosphatase (ALP), osteopontin, and osteocalcin (OCN). 3,4 Sodium-dependent vitamin C transporters 1 and 2 (SVCT1, 2) facilitate the transport of AA, [5][6][7] and sodiumdependent AA transport is required for MC3T3-E1 cells to achieve the millimolar intracellular AA concentration that is necessary for maximal prolyl hydroxylase activity and expression of the osteoblast phenotype. 8 We had demonstrated that SVCT2 instead of SVCT1 is expressed in MC3T3-E1 cells, 9 Ca 2 þ , PO 4 3À , or Zn 2 þ enhances osteoblast-like differentiation through increase of SVCT2 expression and AA uptake, 10,11 and SVCT2 overexpression in MC3T3-E1 cells stimulates mineralization and promotes differential marker genes expression.…”
mentioning
confidence: 99%
“…This is due to an inactivating mutation of Lgulono-γ-lactone oxidase (EC 1.1.3.8), which occurred approximately 40 million years ago (Nishikimi et al, 1994). Absorption of vitamin C occurs primarily in the distal small intestine via active transport through an ascorbate transporter termed the Sodium-dependent Vitamin C Transporter-type 1 (SVCT1, gene product of slc23a1) (Tsukaguchi et al, 1999). This transporter is also present in the renal proximal tubules (Tsukaguchi et al, 1999), where it serves to reabsorb filtered ascorbate.…”
Section: Ascorbate Dietary Requirements and Functionmentioning
confidence: 99%
“…Absorption of vitamin C occurs primarily in the distal small intestine via active transport through an ascorbate transporter termed the Sodium-dependent Vitamin C Transporter-type 1 (SVCT1, gene product of slc23a1) (Tsukaguchi et al, 1999). This transporter is also present in the renal proximal tubules (Tsukaguchi et al, 1999), where it serves to reabsorb filtered ascorbate. Ascorbate circulates in blood at 30-60 μM, but its concentrations in most cells are considerably higher.…”
Section: Ascorbate Dietary Requirements and Functionmentioning
confidence: 99%
“…SLC23A1 is expressed in tissues critical for absorption and reabsorption of vitamin C (kidney, intestinal, and hepatic tissues) [4]. Therefore functional consequences of variations in SVCT1 would impact on dietary requirements and recommendations.…”
Section: Introductionmentioning
confidence: 99%